Pharmacogenetics of beta adrenergic blockers: their clinical significance - Elsayed, Tarek Mohamed Ali (USM, 2009)
Beta adrenergic blockers are (ß-blockers) an important class of drugs for the treatment of various cardiovascular diseases, including hypertension, angina pectoris, arrhythmias, hypertrophic cardiomyopathy, and heart failure. They are also indicated for the treatment of migraine headache, anxiety, tremor, and glaucoma. Individual and ethnic variability has been noted in clinical practice and reported in clinical trials. Many factors are anticipated to affect the extent of variability of response to β-blockers including pharmacodynamic variability and pharmacokinetic variability of the parent compounds, as well as, active constituents. In this review, we will present the studies that examine the effect of genetic variability on the pharmacodynamics of β-blockers.